2001
DOI: 10.1083/jcb.153.5.957
|View full text |Cite
|
Sign up to set email alerts
|

Cooh-Terminal Truncations Promote Proteasome-Dependent Degradation of Mature Cystic Fibrosis Transmembrane Conductance Regulator from Post-Golgi Compartments

Abstract: Impaired biosynthetic processing of the cystic fibrosis (CF) transmembrane conductance regulator (CFTR), a cAMP-regulated chloride channel, constitutes the most common cause of CF. Recently, we have identified a distinct category of mutation, caused by premature stop codons and frameshift mutations, which manifests in diminished expression of COOH-terminally truncated CFTR at the cell surface. Although the biosynthetic processing and plasma membrane targeting of truncated CFTRs are preserved, the turnover of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
88
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(96 citation statements)
references
References 102 publications
(165 reference statements)
8
88
0
Order By: Relevance
“…Little is known about the mechanisms responsible for recognition and degradation of abnormal membrane proteins in the distal compartments of the secretory pathway. A post-ER QC mechanism appears to be responsible for recognition and degradation of cytoplasmic domain mutants of CFTR (Benharouga et al, 2001) and the nicotinic acetylcholine receptor ␣-subunit (Keller et al, 2001). Although we cannot exclude the possibility that the mutant TM might perturb the conformation of the short cytoplasmic tail of HA ϩϩ , resulting in its recognition by cytoplasmic chaperones, our data strongly implicate the mutant TM as the primary signal for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the mechanisms responsible for recognition and degradation of abnormal membrane proteins in the distal compartments of the secretory pathway. A post-ER QC mechanism appears to be responsible for recognition and degradation of cytoplasmic domain mutants of CFTR (Benharouga et al, 2001) and the nicotinic acetylcholine receptor ␣-subunit (Keller et al, 2001). Although we cannot exclude the possibility that the mutant TM might perturb the conformation of the short cytoplasmic tail of HA ϩϩ , resulting in its recognition by cytoplasmic chaperones, our data strongly implicate the mutant TM as the primary signal for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Lines and Transfection-BHK-21 (CCL 10; American Type Culture Collection (ATCC)), COS-1 (CRL-1650; ATTC), MDCK II (CCL-34; ATTC), and CaCo-2 (HTB-37; ATTC) cells were cultured as described previously (10). Pancreatic duct cells PANC-1 (CRL-1469; ATCC) were grown in human tracheal epithelia (9HTE160 Ϫ , designated as HTE), a generous gift of Dr. Dieter Gruenert (Human Molecular Genetics Unit, Department of Medicine, University of Vermont, Burlington, VT), were cultured in Eagle's minimal essential medium and 10% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
“…Soluble proteins were separated on 7-10% SDS-PAGE and transferred to a nitrocellulose membrane. Membranes were probed with the mouse monoclonal anti-HA Ab at 1:10,000 dilution, the M3A7 anti-CFTR Ab at 1:1000 dilution (kindly provided by Dr. N. Kartner (41)), or the monoclonal mouse 24 -1 anti-CFTR Ab (Genzyme Inc.) at 1:1000 dilution and visualized by ECL (Amersham Biosciences) as described (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,36,37 Recent studies indicated that the CFTR C-terminus is not required for the biosynthesis and plasma membrane targeting of CFTR, but indispensable for maintaining the stability of the protein. 38 Benharouga et al 39 could also show that an ERAD-similar mechanism involving the proteasome-ubiquitin pathway may be responsible for the faster turnover and the short residence time at the apical membrane of truncated CFTR. This faster recycling rate of truncated proteins may provide an explanation for the reduced amount of 3905insT CFTR at the apical membrane.…”
Section: Discussionmentioning
confidence: 98%